2010
DOI: 10.1007/s10773-010-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Party Quantum Information Splitting of an Arbitrary Two-Qubit State by Using Six-Qubit Cluster State

Abstract: We propose a scheme for splitting an arbitrary two-qubit state among three parties by using a six-qubit cluster-class state as a quantum channel. Based on two Bell-state measurements (BSMs) and a two-qubit projective measurement, any one of the two agents can reconstruct the original state if he/she collaborates with the other one, whilst individual agent obtains no information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A lot of teleportation schemes have been reported, which took the six particle cluster states as the quantum channel [30,31]. In the literature [30], Nie demonstrated that the deterministic quantum state sharing of a two-atom state can be realized by the six-atom cluster state.…”
mentioning
confidence: 99%
“…A lot of teleportation schemes have been reported, which took the six particle cluster states as the quantum channel [30,31]. In the literature [30], Nie demonstrated that the deterministic quantum state sharing of a two-atom state can be realized by the six-atom cluster state.…”
mentioning
confidence: 99%
“…The QSS of an arbitrary two-qubit state was proposed by Deng et al [22] using two GHZ states. QSS using cluster states was demonstrated by Nie [23], Panigrahi [24,25] and Han [26]. Recently, two qubit QSS was discussed using arbitrary pure or mixed resource states [27] and asymmetric multipartite state [28].…”
Section: Introductionmentioning
confidence: 99%
“…The QIS of an arbitrary two-qubit state was proposed by Deng et al using two GHZ states [14]. QIS of two qubit states using cluster states was demonstrated by Nie [15], Panigrahi [16,17] and Han [18]. Recently, two-qubit QIS was discussed using arbitrary pure or mixed resource states [19] and asymmetric multi-particle state [20].…”
Section: Introductionmentioning
confidence: 99%